Morphological traits in nitrogen fixing heterocytous cyanobacteria: possible links between morphology and eco-physiology - de Tezanos Pinto, Paula (2016)
Heterocytous cyanobacteria are able to fix nitrogen (in heterocytes) and to produce dormant cells (akinetes). Heterocyte and akinete shape, size, and relative position have taxonomical relevance and possibly ecological value too. We collected—from literature and nature—and compared morphological data on vegetative cells, heterocytes, and akinetes across four genera taxonomically separated from Anabaena. In average, heterocyte size doubled that of vegetative cells—probably because of extra cell wall deposition. Heterocyte morphology was remarkably similar across genera, both in size and shape (spherical). The latter may decrease oxygen diffusion from adjoining vegetative cells. Akinetes were huge (one order of magnitude bigger) compared to vegetative cells, probably because of its massive genome replication, extra deposition of wall layers, allocation of storage and number of vegetative cells fused during akinete differentiation. Akinete shape was mostly cylindrical, or oval, but rarely spherical. In line with molecular data, we found morphological differences between Anabaena (non-aerotopated, soil or benthic) and Dolichospermum (aerotopated, planktonic), including vegetative cell size, and akinete size, shape, and relative position to the heterocyte. Differences may relate to adaptations to their contrasting environments (benthic versus planktic). Further research is needed to generalize our results to other heterocytous genera.